2016
DOI: 10.1097/ijg.0000000000000404
|View full text |Cite
|
Sign up to set email alerts
|

Anterior-Chamber Angle and Axial Length Measurements in Normal Chinese Children

Abstract: All angle measurements increased with age and were positively correlated with the ACD in children 7 to 15 years of age. The AL increased logarithmically with age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 22 publications
2
21
0
1
Order By: Relevance
“…We reanalyzed the swept-source ASOCT data (SS-1000 CASIA TM , TOMEY, Nagoya, Japan) obtained from 43 children that were taken in the dark room condition without pupil dilation. [12] Vertical scan images in ASOCT were often disturbed by the eyelids; thus, we selected the clearest horizontal scan images. The ASOCT parameters were evaluated by Y.N.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We reanalyzed the swept-source ASOCT data (SS-1000 CASIA TM , TOMEY, Nagoya, Japan) obtained from 43 children that were taken in the dark room condition without pupil dilation. [12] Vertical scan images in ASOCT were often disturbed by the eyelids; thus, we selected the clearest horizontal scan images. The ASOCT parameters were evaluated by Y.N.…”
Section: Methodsmentioning
confidence: 99%
“…[11] However Jin P et al first reported an increase in IT in parallel with the increasing age of children (7–15 years). [12] The association between IT changes and age or other ocular parameters has not been investigated. Therefore, our study aimed to investigate the IT in children and determine the association between IT and ocular parameters, especially in those children who were also in developing period, thus, this study may lead to an understanding of ocular structural development.…”
Section: Introductionmentioning
confidence: 99%
“…), and only a few such studies have sought to assess the angle in children (Urbak ; Jin et al. ; Fernández‐Vigo et al. ; Tandon et al.…”
Section: Introductionmentioning
confidence: 99%
“…To date most of these angle studies, especially the larger ones, have been performed in adult Asian populations (Usui et al 2011;Shi et al 2012;Hong et al 2013), and only a few such studies have sought to assess the angle in children (Urbak 1999;Jin et al 2016;Fern andez-Vigo et al 2017;Tandon et al 2017). This lack of literature data also means that the possible effects of several factors such as gender, age, refractive error, angle or TM measurements on the size of the anterior chamber angle and its structures have yet to be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study showed that inter-gender differences in AC indices in patients with Down syndrome have a pattern similar to normal individuals, and females have shallower AC compared to males; this difference is independent of age. [ 20 22 25 26 ] In addition, the ACA gender difference was only observed in the temporal quadrant, and there were no inter-gender differences in the other three meridians. In a study by Aslan,[ 17 ] the correlation of AC indices to gender was not evaluated but Haugen et al .…”
Section: Discussionmentioning
confidence: 88%